2011
DOI: 10.1016/j.jvs.2011.03.259
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, outcomes, and clinical manifestations of spinal cord ischemia following thoracic endovascular aortic repair

Abstract: Spinal cord ischemia after TEVAR is an uncommon, but important complication. Preoperative renal insufficiency was identified as a risk factor for the development of SCI. Early detection and treatment of SCI with blood pressure augmentation alone or in combination with CSF drainage was effective in most patients, with the majority achieving complete, long-term neurologic recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
148
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(153 citation statements)
references
References 43 publications
4
148
1
Order By: Relevance
“…Interestingly, in a prospective observation study, Maeda et al [14] showed that a greater percentage of patients with ischemic spinal cord injury following thoracic endovascular aneurysm repair (TEVAR) had a delayed paraplegia (66.7 %) than following traditional treatment (16.7 %). Similar results were also reported by Ullery et al [15]. Thus, it is expected that as TEVAR increases in the future, so will the incidence of delayed onset paraplegia.…”
supporting
confidence: 89%
“…Interestingly, in a prospective observation study, Maeda et al [14] showed that a greater percentage of patients with ischemic spinal cord injury following thoracic endovascular aneurysm repair (TEVAR) had a delayed paraplegia (66.7 %) than following traditional treatment (16.7 %). Similar results were also reported by Ullery et al [15]. Thus, it is expected that as TEVAR increases in the future, so will the incidence of delayed onset paraplegia.…”
supporting
confidence: 89%
“…Classification of DTAA according to the extension. 202 with a significant reduction in peri-operative mortality ( 216 Several reports confirm that specific anatomical conditions may represent potential risk factors for postoperative SCI. These include planned coverage of the thoracic aorta over more than 200 mm or involving the level T8-T12, previous abdominal aortic surgery with ligation of lumbar arteries, an occluded hypogastric artery, and, in the emergency setting the need for LSA coverage not amenable to revascularisation.…”
Section: Recommenda On 39mentioning
confidence: 99%
“…In 2011 Ullery BW et al [14] in 424 patients treated between 2002 and 2010 reported SCI rate of 2.8%.…”
Section: What Is the Incidence Of Spinal Cord Ischemiamentioning
confidence: 98%
“…Concluded " … of the prespecified factors investigated for association with SCI, only percentage of aortic coverage was significantly associated with the incidence of SCI; adjusted odds ratio per 10% increase in aorta covered = 1.78 [95% CI 1.81 -2.71], p = 0.007". In 2011 Ullery BW, Cheung AT, Fairman RM et al [14]. In a study of 424 patients un- In summary the factors that are clearly demonstrated within the scientific literature to be predictors for development of SCI are the extent of coverage of the aorta with a threshold of 205 mm absolute coverage or doubling for every 10% of aortic coverage.…”
Section: What Are the Risk Factors For Spinal Cord Ischaemiamentioning
confidence: 99%